Microstructure of Geopolymer Concrete Based on Fly Ash Using M-Sand - Anuradha, R.; Sreevidya, V.; Venkatasubramani, R. (Asian Journal of Chemistry, 2012)
Geopolymers prepared from a class F-fly ash and a mixed alkali activator of sodium hydroxide and sodium silicate solution were investigated. A high compressive strength was obtained when the modulus of the activator viz., molar ratio of SiO2/Na2O was 2.5. Any presence of the temporary phase with different composition was not found between geopolymer and aggregate as it is at the concretes from Portland cement. Geopolymer composition is almost the same in the close nearness even in the geopolymer matrix. Elastic modulus evaluated for the mixed geopolymeric concrete was found to be E = 4389 (fck)0.535 Mpa. Such result is comparable (a little bit lower) to ordinary Porland cement pastes.